(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A person’s thoughts, ideas and feelings are expressed through speaking and writing which are commonly termed as expressive skills. Through these skills, teachers are able to assess the level of understanding of the learners on a particular lesson that was taught. Employing the descriptive –quantitative-correlational research design, this study aims to assess the level of the speaking and writing skills of the six grader learners among the selected schools in one of the Division in Zamboanga Peninsula. Furthermore, it also sought to know if significant correlation exists between the two expressive skills. This study enlisted 180 pupils from different public schools which were chosen through stratified sampling. Using the series of pictures taken from the Language Expressway 6 which is a standardized instrument, the respondents where ask to narrate a story out of the pictures through speaking and writing. Their oral and written output were then rated by the three English language teachers using the assessment matrix of DepEd Order no.8, series of 2015. The findings of the study concludes that the speaking and writing skills of the six grader learners falls below the level of 75% which is the national passing rate of public schools in the Philippines. Moreover, a positive correlation was noted between the two expressive skills. Hence, the Ha is being accepted. Therefore, it is safe to say that the learners did not meet the level of speaking and writing that is expected of them. This result may be associated with the implementation of the Mother Tongue Based instruction from Grade I-III which focuses on the mastery of the L1 of the learners. Perhaps, we may consider that reason for the present level of speaking and writing among the six grader learners.